(untitled) (FUDMA JOURNAL OF SCIENCES, 2022)
This study mapped out the agricultural land suitability in Zaria using Geospatial Techniques (GT) with a view to highlight areas of improvement in production to enhance food security. The Agricultural Land Suitability (ALS) is the fitness of a land to a specific crop. ALS selects the land that best suits and supports a crop optimal yield, by matching the land qualities with the crop’s requirements; hence increasing productivity per unit land at minimum inputs and cost. The agricultural lands in the study area were identified and mapped as well as the biophysical land qualities that influence rice cropping. The prevalent biophysical land qualities were matched with the rice requirements; and evaluation of the agricultural land suitability was done using GT and Multi Criteria Decision Making (MCDM) modelling approach. Food and Agricultural Organization (FAO) method to land suitability evaluation was adopted via GT; which entails delineating the study area into highly suitable (S1), moderately suitable (S2), marginally suitable (S3), temporarily not suitable (N1), and permanently not suitable (N2). The study findings were that about 5% of the area is highly suitable, 9% very suitable, 18% moderately suitable, 55% is marginally suitable, and 13% not suitable. The results of this study can be used by individuals, private organizations, and government to increase agricultural productivity in the study area for sustainable rice farming in order to optimize yield as well as mitigate degradation and erosion